Confronting animal exploitation : grassroots essays on liberation and veganism - Socha, Kim; Blum, Sarahjane (Academic & Nonfiction Books anthology., 2013)
This volume broadens animal liberation dialogues by offering the arguments, challenges, inspiration and narratives of grassroots activists. The essays show what animal advocacy looks like from a collective of individuals living in and around Minnesota's Twin Cities.